E-COMMERCE DEVELOPMENT: FOREIGN EXPERIENCE - KOTELNIKOVA, Iuliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Modern economic processes and systems are subject to the influence of two of the most important modern processes: digitization and globalization. Digitalization is increasingly influencing all spheres of the economy and its individual segments. In particular, e-commerce has shown high growth rates in recent years. In the context of the digitalization of the economy, the technological component of this trade segment is being strengthened: new tools supporting artificial intelligence, big data analytics, automation of business processes are being introduced, and platform solutions are being developed. In parallel, the processes of integration and globalization of the economy stimulate the emergence of new types, forms of sale and distribution channels of goods on the global market. One of these forms of trade is electronic trade. Currently, e-commerce is one of the most dynamically developing segments of the trade sphere and the national economy in any country as a whole, which characterizes the impact of digital changes in modern life. Along with the popularization of e-commerce and changes in the consumption habits of the main groups of Internet consumers, e-commerce service providers provide professional services in all aspects of transactions, effectively reducing transaction costs, which encourages more and more autonomous traditional enterprises to participate in e-commerce by actively launching the Internet during transformation For modern companies, e-commerce is already a necessary advertising tool. Electronic commerce connects all links of the trade process with its participants (consumers, intermediaries, manufacturers, etc.) in a single chain, since it includes the need to adhere to the principles of standardization, automation of business processes, which as a result provides a high-quality level of information, reducing the costs of its participants and turning the whole process into a convenient means of promoting goods. E-commerce is based on the structure of traditional commerce, and the use of electronic networks adds flexibility to it. Using digital information in computer networks, e-commerce offers fundamentally new opportunities for doing business, for example, it facilitates the cooperation of business groups, improves relations with consumers, removes limitations in time and space, etc.